IMPLEMENTASI SUPERVISI AKADEMIK PIMPINAN MAN 1 KOTA PAYAKUMBUH DI MASA PANDEMI COVID 19 - Ridha Albiy; Sufyarma Marsidin; Rifma Rifma (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
The propose of this study is the accomplishment of the academic supervision of the madrasah principal during the covid 19 pandemic. The study uses phenomenological qualitative method. The research was conducted at MAN 1 Kota Payakumbuh for the 2020-2021 Academic Year. Data collection use interview, observation, and documentation. Principal of the madrasah and entire school which include in this study are the source of data. The accomplishment of academic supervision is carried out in three levels are first level in the form of contracts, second level in the form of accomplishment, and third lebel in the form of strengthening. The results showed that the implementation of academic supervision during the COVID-19 pandemic when the green zone was going well. Although learning is carried out in rotation every week, it does not reduce the spirit of the madrasah principal to improve the quality of the learning process. Learning activities during the pandemic era were carried out with 2 models, namely the online model during the red zone and face-to-face with a system of alternating classes every week when the green zone returned.